Vehicle seat slide rail decorative cover mounting structure and vehicle - SHI QIGUO; LONG GANGQI (2023)
The invention relates to the technical field of vehicles, in particular to a vehicle seat sliding rail decorative cover mounting structure and a vehicle. The vehicle seat slide rail decorative cover mounting structure comprises a slide rail assembly, a fastener, a slide rail decorative cover and a shielding cover, wherein the slide rail assembly is connected to a vehicle body; the fastener penetrates through the sliding rail assembly and the vehicle body so as to connect the sliding rail assembly with the vehicle body. The sliding rail decorative cover is arranged at the end of the sliding rail assembly in a sleeving mode and connected with the sliding rail assembly. The shielding cover is located in the sliding rail assembly and covers the fastener, one end of the shielding cover is connected with the sliding rail decorative cover in a clamped mode, and the other end of the shielding cover is connected with the sliding rail assembly in a limiting mode. The fastening device has the beneficial effects that by